A fluid–solid momentum exchange method for the prediction of hydroelastic responses of flexible water entry problems - Tavakoli, Sasan; Mikkola, Tommi; Hirdaris, Spyros (Journal of fluid mechanics, 2023)
The paper presents a Fluid Structure Interaction (FSI) method for hydroelastic water entry. The method assumes that the momentum exchange between the fluid and solid body can be used for the calculation of pressure, deformation and stresses arising during impact. The flexible fluid–structure interactions of flat plates entering water are solved using a computational code that employs the finite volume method to discretise both fluid and solid equations. This provides a better matching of momentum on the fluid–solid interface. The momentum arising in the solid body that emerges after the impact is defined as the momentum exchange, and is shown to increase linearly under the increase of non-dimensional impact speed. The ratio of the maximum pressure arising in an elastic body entering water to that of a rigid body is termed relative pressure and is shown to decrease linearly as a function of momentum exchange. The latter verifies the main hypothesis of this paper, namely that ‘the pressure acting on an elastic body can be predicted using an unsophisticated equation that uses the momentum exchange.’ The deformation and stresses arising in elastic plates entering water are demonstrated to be functions of momentum exchange and can be found using simple equations formulated via parametrisation of data. It is concluded that subject to further validation, the method could be extended for the prediction of hydroelastic response of other sections/bodies entering water.